2018
DOI: 10.1371/journal.pone.0198845
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of notification systems for infectious diseases: A systematic literature review

Abstract: IntroductionTimely notification of infectious diseases is crucial for prompt response by public health services. Adequate notification systems facilitate timely notification. A systematic literature review was performed to assess outcomes of studies on notification timeliness and to determine which aspects of notification systems are associated with timely notification.MethodologyArticles reviewing timeliness of notifications published between 2000 and 2017 were searched in Pubmed and Scopus. Using a standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…10 According to a 2018 systematic review, electronic reporting and web-based systems results in more timely notifications than post and facsimile. 16 This is consistent with the results of this audit which demonstrated that 96.4% of routine cases notified by doctors online were received within five days. However, only 23.9% of routine cases in 2016 and 2017 were notified via this method.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…10 According to a 2018 systematic review, electronic reporting and web-based systems results in more timely notifications than post and facsimile. 16 This is consistent with the results of this audit which demonstrated that 96.4% of routine cases notified by doctors online were received within five days. However, only 23.9% of routine cases in 2016 and 2017 were notified via this method.…”
Section: Discussionsupporting
confidence: 90%
“…3 ELR requires information technology infrastructure to code disease diagnoses and transfer data from pathology laboratory databases. 16 While implementation can be challenging for public health departments, ELR has been credited with improving the timeliness of infectious disease surveillance internationally. 17,18 Given the benefits of ELR, at the DHHS a staged commencement of a largerscale ELR system is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the nding of Rebecca Wurtz and Bruce J. Cameron on electronic laboratory reporting (ELR). In their report, ELR increased the speed of completeness of the reporting [26,27]. Completeness of reporting in our context is not diseased speci c or case enumeration, [28] but is based on the number of health facilities sending IDSR reports to the next level within agreed deadlines [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…Tackling a pandemic is surely not an easy task. Based on the protocols established by the WHO, every nation can be a "Noah", setting up surveillance system for diseases and notifying the WHO in a timely manner to ensure adequate preparedness plans [29][30][31] . With leaders over the world indicating that "failure is not as option", it is indeed dire times now as the spread of the virus cripples cities around and crashes the economies worldwide [32,33] .…”
Section: Main Textmentioning
confidence: 99%